Can rehabilitation improve the health and well-being in Friedreich's ataxia: a randomized controlled trial?. (May 2018) - Milne, Sarah C; Corben, Louise A; Roberts, Melissa; Murphy, Anna; Tai, Geneieve; Georgiou-Karistianis, Nellie; Yiu, Eppie M; Delatycki, Martin B
Objective: To determine the effectiveness of a six-week rehabilitation programme followed by a home exercise programme for Friedreich's ataxia. Design: Randomized, delayed-start control single-blind trial. Setting: Outpatient rehabilitation centre. Subjects: Ambulant or non-ambulant individuals with Friedreich's ataxia. Intervention: Participants were randomized to a six-week outpatient rehabilitation programme, immediately (intervention group) or after a six-week delayed-start (control group). The rehabilitation was followed by a six-week home exercise programme. Main measures: The primary outcome was the Functional Independence Measure. Other measures included the Friedreich Ataxia Impact Scale and the Friedreich Ataxia Rating Scale. Outcomes were administered at baseline, 6, 12 and 18 weeks. Results: Of 159 individuals screened, 92 were excluded and 48 declined to participate. A total of 19 participants were enrolled in the study. There was no significant difference in Functional Independence Measure change from baseline to six weeks in the intervention group (mean ± standard deviation, 2.00 ± 3.16) as compared to the control group (0.56 ± 4.06). Change in the Friedreich Ataxia Impact Scale body movement subscale indicated a significant improvement in health and well-being in the intervention group compared to the control group ( P = 0.003). Significant within-group improvements in the Friedreich Ataxia Impact Scale and the motor domain of the Functional Independence Measure post-rehabilitation were not sustained post-home exercise programme. Conclusion: Our study indicates that rehabilitation can improve health and well-being in individuals with Friedreich's ataxia; however, a larger study is required to have sufficient power to detect a significant change in the most sensitive measure of function, the motor domain of the Functional Independence Measure.